(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2025)
This research focuses on conducting load flow and short-circuit analysis on a segment of central part of Nepalese power system, specifically from New Butwal substation to Dhalkebar substation. The analysis was initially carried out on a standard IEEE 5-bus system to validate the approach and methodology, followed by its application to the selected section of Nepalese power grid. Primary objective of this research was to evaluate the system’s performance under various faulty conditions and identify potential vulnerabilities. Nepal’s power system has been struggling with significant challenges, such as frequent outages, aging infrastructure, and a rapidly increasing electricity demand. This research applied Electrical Transient Analyzer Program software to construct and simulate the system, perform load flow studies, and analyze short-circuit scenarios on both IEEE 5 bus system and a central section of the Nepalese grid, changing faulty locations. It aimed to assess the impact of faults on different buses, identify sensitive nodes, and recommend strategies to minimize disruptions and maintain grid stability. Key findings revealed that Parwanipur 2 bus exhibited high sensitivity to faults in terms of current, while Dhalkebar bus was vulnerable in terms of voltage. These results indicated that the vulnerable system components require upgradation, such as the installation of surge protection devices, addition and upgradation of transmission lines, substations, transformers, are essential to mitigate potential risks. Overall, this research contributes to ongoing efforts to strengthen Nepal’s power system by providing valuable insights that can enhance future infrastructure development and operational strategies, ultimately enhancing the grid’s resilience and performance.